Characterisation of liver chemistry abnormalities associated with pazopanib monotherapy: A systematic review and meta-analysis of clinical trials in advanced cancer patients. Issue 10 (July 2015) - Powles, Thomas; Bracarda, Sergio; Chen, Mei; Norry, Elliot; Compton, Natalie; Heise, Mark; Hutson, Thomas; Harter, Philipp; Carpenter, Christopher; Pandite, Lini; Kaplowitz, Neil
Abstract Drug-induced liver chemistry abnormalities, primarily transaminase elevations, are commonly observed in pazopanib-treated patients. This meta-analysis characterises liver chemistry abnormalities associated with pazopanib. Data of pazopanib-treated patients from nine prospective trials were integrated (N = 2080). Laboratory datasets were used to characterise the incidence, timing, recovery and patterns of liver events, and subsequent rechallenge with pazopanib. Severe cases of liver chemistry abnormalities were clinically reviewed. Multivariate analyses identified predisposing factors. Twenty percent of patients developed elevated alanine aminotransferase (ALT) >3×ULN. Incidence of peak ALT >3–5×ULN, >5–8×ULN, >8–20×ULN and >20×ULN was 8%, 5%, 5% and 1%, respectively. Median time to onset for all events was 42 days; 91% of events were observed within 18 weeks. Recovery rates based on peak ALT >3–5×ULN, >5–8×ULN, >8-20×ULN and >20×ULN were 91%, 90%, 90% and 64%, respectively. Median time from onset to recovery was 30 days, but longer in patients without dose interruption. Based on clinical review, no deaths were associated with drug-induced liver injury. Overall, 38% of rechallenged patients had ALT elevation recurrence, with 9-day median time to recurrence. Multivariate analysis showed that older age was associated with development of ALT >8×ULN. There was no correlation between hypertension and transaminitis. Our data support the current guidelines on regular liver chemistry tests after initiation of pazopanib, especially during the first 9 or 10 weeks, and also demonstrate the safety of rechallenge with pazopanib.